Meaning of well-being of older institutionalized persons in abandonment situation - Wendy Sindy Nallely Flores Martínez; María de Jesús Jiménez González; Norma Elvira Moreno Pérez; Raúl Fernando Guerrero-Castañeda
ABSTRACT Objective: To understand the meaning of well-being of older persons in situation of abandonment. Methods: a qualitative phenomenological study, carried out in a nursing home in Tepic, Nayarit, from 2017 to 2019. Intentional sampling with 12 older persons aged 60 and above. Data collection occurred by phenomenological interview. The ethical criteria of the General Health Law were respected. Participants signed the Informed Consent Form. Data analysis took place through phenomenological analysis. Results: four themes have emerged: 1. Living Activities of Daily Living; 2. Attention to physical needs; 3. Coexistence; 4. Spirituality experience. Conclusion: for older persons, living institutionalized implies a process of adaptation and transformation to their context and state of life, restructuring their needs that provide well-being. It is important to approach these scenarios to establish ways of experiencing aging that favor a full quality of life.